The Legality of Drones and Lethal Automatous Weapon Systems: Is Skynet a viable possibility for the future? - Oakes, Kyle Leif (My University, 2016)
The purpose of this paper is to look at the interplay between the current legal aspects of modernized warfare and the military industrial complex. Through analyzing the current and historical legal documents of various international organizations, specifically those of the International Committee of the Red Cross, and national governing bodies, clarification pertaining to the legality of these systems can be found. Furthermore, by looking at corporate information relating to research and development as well as the overall global defense industry legal norms relating to modern military techniques and practices can be found. This paper will not focus on the morality and ethical questions of utilizing autonomous and semi-autonomous weapons systems; rather, it will look purely at the legality of them based on usage trends over the last couple decades. Through the study of current conflicts and warfare, this paper will show that the utilization of armed drones do in fact fall under the laws of armed conflict, whereas the ambiguity of lethal autonomous weapon systems cause them to fall outside the purview of international humanitarian law for the time being. Since these systems do not fall under the laws of armed conflict, it is necessary for the international community to create new sets of laws and regulations prior to the mass implementation of lethal autonomous weapon systems, as a means to break the trend of reactionary laws.